Enhancing Climate-Resilient Farming in Indonesia: The Roles of Crop Diversification, Agroforestry Adoption, Environmental Literacy, and Farmer Cooperative Participation - Agatha W. Widati; Yohanes Kamakaula; Trees Augustine Pattiasina (Westscience Press, 2026)
This study examines the role of crop diversification, agroforestry implementation, environmental literacy, and farmer cooperative participation in promoting climate-resilient agriculture in Indonesia. Climate change has increasingly affected agricultural productivity, environmental sustainability, and farmer livelihoods through droughts, floods, irregular rainfall patterns, and land degradation. A quantitative research approach was employed using a survey of 250 farmers from several agricultural regions in Indonesia. Data were collected using structured questionnaires with a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 4). The findings indicate that crop diversification positively and significantly influences climate-resilient agriculture Agroforestry implementation was found to have the strongest influence. Environmental literacy also demonstrated a significant positive effect, while farmer cooperative participation significantly affected climate-resilient agriculture. The model showed strong explanatory power with an R-square value of 0.742, indicating that the independent variables explained 74.2% of the variance in climate-resilient agriculture. The results highlight the importance of integrating sustainable farming practices, environmental awareness, and institutional collaboration to strengthen agricultural resilience and sustainability in Indonesia.